Integrating voice and data over local area network in UPM - Mohd Ali, Borhanuddin (1990)
The recent years have seen a flurry of new activities particularly in the field of computers and communications. The power of mainframes of yesteryears are now available on our desktops, thanks to VLSI technology that makes it all possible in the first place. With the proliferation of new and more powerful computers for more and more sophisticated applications, there is a need to network them together to share resources and to port our softwares around hence to reduce development time. This paper will describe some of the new technologies that has been procured and how they are being integrated with some of the 'dinosaurs' still surviving in the Faculty. A discussion of how various computer systems are networked together are also made. Finally, the paper will end with a discussion on the development of a prototype Packet Voice Terminal which will allow voice communication over the packet based Ethernet Local Area Network. Data and voice has a completely conflicting characteristics : voice is real time and contains a lot of redundancies therefore it cannot tolerate delays but can tolerate some losses of speech segments, whereas data is the complete opposite-it can tolerate delays but not errors and losses. A compromise will have to be made to accomodate the two kinds of traffic.